2017
DOI: 10.1515/abcsb-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Karyological and Molecular Characteristics of Festuca arietina Klok. – a Neglected Psammophilous Species of the Festuca valesiaca agg. from Eastern Europe

Abstract: Until recently, Festuca arietina was practically an unknown species in the flora of Eastern Europe. Such a situation can be treated as a consequence of insufficient studying of Festuca valesiaca group species in Eastern Europe and misinterpretation of the volume of some taxa. As a result of a complex study of F. arietina populations from the territory of Ukraine (including the material from locus classicus), Belarus and Lithuania, original anatomy, morphology and molecular data were obtained. These data confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Those species which have continuous sclerenchyma are classified into the eu-ovina aggregate. These taxa can be identified easily based on their characteristic tissue structure and molecular genetic analyses [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those species which have continuous sclerenchyma are classified into the eu-ovina aggregate. These taxa can be identified easily based on their characteristic tissue structure and molecular genetic analyses [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…dominii (Krajina) P. Šmarda and [25] clarified the taxonomic status of the species and concluded that it was a subspecies of F. psammophila (Čelak.) Fritsch (which currently occurrs only in pine forests in Northern Europe [17]). Therefore, the accepted name of the species is F. psammophila subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Those taxa of Festuca species in the Carpathian Basin which have bowed base and stem leaves are identified and mentioned by various authors as belonging to the aggregation of Festuca ovina (Adler et al, 1994;Horánszky et al, 1971;Májovszký, 1962;Patzke, 1968;Soó, 1973;Stace et al, 1992;Săvulescu, 1972;Schwarzová, 1967;Armonien et al, 2010). These taxa can be identified easily based on their characteristic tissue structure and molecular genetic analyses (Bednarska et al, 2017;Galli et al, 2001Galli et al, , 2006Šmarda et al, 2007;Šmarda, 2008;Šmarda and Kočí, 2003;Pawlus, 1985). Pawlus (1985) separated a new series within the Festuca genus.…”
mentioning
confidence: 99%